Haemoglobin, Serum Ferritin and Serum-Mineral Levels of the Elderly People: A Comparison between Urban and Rural Community - Dillruba, Nurun Nahar; Barua, Sagarmay (Bangladesh Journal of Nutrition, 2014)
Abstract available on PDF Bangladesh J. Nutr. Vol. 26-27, December 2014